2022
DOI: 10.1371/journal.pone.0279619
|View full text |Cite|
|
Sign up to set email alerts
|

The cross-sectional association of stressful life events with depression severity among patients with hypertension and diabetes in Malawi

Abstract: Depressive disorders are a leading cause of global morbidity and remain disproportionately high in low- and middle-income settings. Stressful life events (SLEs) are known risk factors for depressive episodes and worsened depressive severity, yet are under-researched in comparison to other depression risk factors. As depression is often comorbid with hypertension, diabetes, and other noncommunicable diseases (NCDs), research into this relationship among patients with NCDs is particularly relevant to increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Previous studies on adolescent depression have primarily focused on serotonin and hypothalamic–pituitary–adrenal (HPA) axis dysregulation hypotheses [ 7 , 8 ]. In recent decades, mounting evidence suggests that inflammation may play a significant role in depression, as evidenced by a higher prevalence of depression in patients with immune diseases, multiple sclerosis, and diabetes [ 9 , 10 ]. Anti-inflammatory treatments, such as infliximab and minocycline, have also show significant antidepressant effects [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on adolescent depression have primarily focused on serotonin and hypothalamic–pituitary–adrenal (HPA) axis dysregulation hypotheses [ 7 , 8 ]. In recent decades, mounting evidence suggests that inflammation may play a significant role in depression, as evidenced by a higher prevalence of depression in patients with immune diseases, multiple sclerosis, and diabetes [ 9 , 10 ]. Anti-inflammatory treatments, such as infliximab and minocycline, have also show significant antidepressant effects [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on adolescent depression have primarily focused on serotonin and hypothalamic-pituitary-adrenal (HPA) axis dysregulation hypotheses (7,8). However, in recent decades, growing evidence has shown that in ammation may play an important role in depression, with a higher prevalence of depression in patients with immune diseases, multiple sclerosis, and diabetes (9,10). Studies have also shown that anti-in ammatory treatments, such as in iximab and minocycline, also show signi cant antidepressant effects (11).…”
Section: Introductionmentioning
confidence: 99%